2022
DOI: 10.1186/s12986-022-00648-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of heat-transformed green tea extract through the activation of adipose tissue thermogenesis

Abstract: Background Adipose tissue thermogenesis is a potential therapeutic target to increase energy expenditure and thereby combat obesity. The aim of the present study was to investigate the thermogenic and anti-obesity effects of heat-transformed green tea extract (HTGT) and enzymatically modified isoquercetin (EMIQ). Methods Immortalized brown pre-adipocytes and C3H10T1/2 cells were used for in vitro analyses. A high-fat diet (HFD)-induced obesity mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Epigallocatechin gallate (EGCG) is a prominent phytochemical found in green tea extract, and approximately half of EGCG undergoes epimerization to form gallocatechin gallate (GCG) during the heat treatment process [11]. A previous study demonstrated the effects of heat-treated green tea extract (HTGT) on visceral fat and hepatic triacylglycerol in rats [12], while our group confirmed that HTGT induces significantly higher expression of UCP1 in brown adipocytes, compared to green tea extract (GTE), due to its elevated content of GCG [13]. Enzymatically modified isoquercitrin (EMIQ) refers to the enzymatic derivatives of rutin, where glucose-rhamnose is attached to the position 3 of the quercetin glycosides [14,15].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Epigallocatechin gallate (EGCG) is a prominent phytochemical found in green tea extract, and approximately half of EGCG undergoes epimerization to form gallocatechin gallate (GCG) during the heat treatment process [11]. A previous study demonstrated the effects of heat-treated green tea extract (HTGT) on visceral fat and hepatic triacylglycerol in rats [12], while our group confirmed that HTGT induces significantly higher expression of UCP1 in brown adipocytes, compared to green tea extract (GTE), due to its elevated content of GCG [13]. Enzymatically modified isoquercitrin (EMIQ) refers to the enzymatic derivatives of rutin, where glucose-rhamnose is attached to the position 3 of the quercetin glycosides [14,15].…”
Section: Introductionsupporting
confidence: 61%
“…In our previous study, we reported the anti-obesity effects of the combined treatment of HTGT and EMIQ. However, previous studies primarily focused on the short-term effects of the HTGT and EMIQ combination in terms of anti-obesity properties [13]. Furthermore, investigations into their in vivo synergistic effects and molecular mechanisms have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…The co-treatment administered to HFD-induced obese mice also increased the expression of brown adipocyte markers and mitochondrial proteins in adipose tissue. After 2 weeks, mice lost 3% body weight and 7.09% body fat, while energy expenditure increased by 8.95% (Im et al, 2022). Bolin et al (2020) also found that a polyphenol-rich green tea extract induced thermogenesis in mice, decreased body weight, adipocyte size, and insulin resistance, increased energy expenditure, BAT thermogenesis, and stimulated browning in subcutaneous WAT.…”
Section: Promotion Of Thermogenesismentioning
confidence: 91%
“…In a recent study by Im et al [ 55 ] in mice also, a synergistic effect of EMIQ in combination with a heat-transformed green tea extract (100 + 100 mg/kg bw) was observed in the reduction of body weight, fat mass, and adipocyte size. The therapeutic effects were comparable to that of mirabegron (10 mg/kg bw), an agonist of the β3-AR signaling pathway, the primary regulatory mechanism involved in lipolysis.…”
Section: Bioactivitymentioning
confidence: 92%